(untitled) (Research, Society and Development, 2022)
The conurbation zones constitute themselves as a result of spatial concentration of activities and people in urban agglomerations, a process that takes place in urban centers with high expansion rate, phenomenon observed when a city absorbs urban centers which are located in its proximities, thus transforming the social configuration and structure of cities, in order to integrate economically by maintaining an intense flow of capital, goods and people. Juazeiro and Petrolina are considered medium range cities that share one common economical and populational dynamic between each other, thus being considered “conurbated” cities. This analysis has as general aim to historically contextualize the cities of Juazeiro and Petrolina, having as aid the following specific goals: to verify the social and demographic indicators of Juazeiro and Petrolina, and to understand the dynamics of the formal labor market in both cities between the years of 2015 and 2019. The offer of employment has been increasing during the years 2015 to 2019, both in Juazeiro and in Petrolina, which implies the possibility of greater income distribution for the population, which can enable an improvement in the quality of life of the residents of the two cities. The agricultural sector can be pointed out as the main responsible for this performance.